Feasibility of Immunosuppressant Drug Monitoring by a Microsampling Device. (19th November 2019) - Gruzdys, Valentinas; Merrigan, Stephen D; Johnson-Davis, Kamisha L
Abstract: Background: Therapeutic drug monitoring (TDM) for immunosuppressive (ISP) drugs is an important component of organ and tissue transplantation and chemotherapy management. Whole blood is the specimen type for the quantitative analysis of cyclosporine A, everolimus, sirolimus, and tacrolimus. Some alternatives to venous whole blood samples have the potential to reduce blood volume requirements and simplify sample collection and transport. Methods: The feasibility of ISP drug (cyclosporine A, everolimus, sirolimus, and tacrolimus) monitoring via microsampling device (Mitra TM, Neoteryx) was assessed by comparing venous samples collected and extracted using microsampling device to conventional extraction procedure. Analysis was performed by LC-MS/MS. Results: All analytes were found to be linear across the measurement range of 22.7–937.0 ng/mL (18.9–779.1 nmol/L) for cyclosporine A, 2.3–44.2 ng/mL (2.4–46.1 nmol/L) for everolimus, 2.2–47.2 ng/mL (2.4–51.6 nmol/L) for sirolimus, and 2.2–41.3 ng/mL (2.7–51.4 nmol/L) for tacrolimus. Imprecision was evaluated at concentrations within the therapeutic range and was found to be 10.1% and 5.8% for cyclosporine A, 10.0% and 10.0% for everolimus, 15.0% and 11.9% for sirolimus, and 6.8% and 8.5% for tacrolimus. Method comparison (n = 30 for each analyte, using Deming regression) indicated slopes of 1.08, 1.02, 0.90, and 1.15 and intercepts of −12.8 ng/mL (−10.7 nmol/L), 0.8 ng/mL (0.8 nmol/L), 1.5 ng/mL (1.7 nmol/L), and −0.3 ng/mL (−0.3 nmol/L) for cyclosporine A, everolimus, sirolimus, and tacrolimus, respectively. Conclusions: This feasibility study demonstrates that precision and bias of ≤15% can be achieved for microsampling-based ISP monitoring.